Health Literacy on Diabetes and Hypertension and Health Behavior among the Elderly in the Upper Central Region of Thailand - Siriphakhamongkhon, Sawanya (Journal of Disease and Health Risk DPC.3, 2023)
The trend among the elderly is toward more and more chronic diseases. Therefore, the impact will increase as the country evolves into an aging society. The two objectives of the study were to investigate the factors related to health literacy and health behaviors and to analyze a model of the causal relationship that influences health behaviors in the elderly. The research design was a mixed-methods study, including a qualitative study in which data were collected through focus group discussions and in-depth interviews with 12 key informants who are aging healthily using a snowball sampling technique, combined with nonparticipant observations, and a quantitative study in which 400 samples between the ages of 60and 79 were selected using multistage random sampling with the interview forms. Data were collected between May and September 2022 and analyzed using content analysis, descriptive statistics, and a structural equation model. The research results can be summarized as follows: The key informants practiced good health behaviors on a daily basis in terms of food consumption, exercise, alcohol and beverages, and cigarette smoking. They were able to adjust and evaluate their health literacy to improve their health. The factors that were positively associated with health behaviors were health literacy (0.39), beliefs and attitudes (0.26), knowledge received (0.21), year of education (0.14), status (0.12), knowledge (0.10), income (0.09), health history (0.09), and neighborhood (-0.13) at a significant level (p-value < 0.05, 0.01, 0.001). The model of causal relationship influencing health behavior showed that health literacy had a direct influence of 58.0 percent and knowledge, belief and attitude, and health literacy had an indirect influence of 26.0 percent each. All variables in the model could be used to explain the health behavior of 33 percent. The model developed has relevance to the empirical data (χ2 = 45.757, P = 0.055, DF=32, CMIN/DF = 1.430, RMR = 0.167, GFI = 0.980, AGFI = 0.960, RMSEA = 0.033). The relevant agencies should use the results of this study to promote health behaviors in the aging population by prioritizing implementation based on the factors identified in this study.